şçi Tarafından Yapılan ve Çekince (İhtirazi Kayıt) İçeren Fesih Bildiriminin (İstifa) Geçerliliği Sorunu - (:unkn) unknown (My University, 2019)
İfa anında borcun bütünüyle sona ermesini engelleyen bir irade açıklaması olarak tanımlanabilecek çekince (ihtirazi kayıt) alacaklıya ait bir haktır. Genellikle borçlar hukuku ve ticaret hukuku disiplinleriyle özdeşleştirilen bu kurum, iş hukukunda da yer yer uygulama alanı bulmakta olup; iş ilişkisinde çekince hakkı, çoğunlukla işçi tarafından kullanılmaktadır. İşçinin çekince koyduğu belgeler arasında uygulamada istifa dilekçesi olarak bilinen süreli veya yazılı fesih bildirimi önemli bir yer tutmaktadır. Çekince işçinin süreli veya usulsüz fesih bildiriminin, duruma göre işçinin haklı nedenle derhal feshine veya işverenin usulsüz ya da haksız feshine dönüşmesini sağlamakta; böylece işçi kıdem tazminatı, ihbar tazminatı ve işe iade istemi gibi feshe bağlı alacak ve haklardan yoksun kalmamaktadır. Yargıtay’ın yerleşik uygulamasında, çekince içeren istifa dilekçelerinin geçerliliği özenle denetlenmekte ve bu bağlamda, çekincede geçen ifadenin genel ve özel nitelikte olması arasında herhangi bir ayırıma gidilmemektedir. Ne var ki işçinin istifa dilekçesine “...tüm yasal haklarım saklıdır...” tarzında bir çekince koyduğu bir uyuşmazlıkta İstanbul Bölge Adliye Mahkemesi 29. Hukuk Dairesi, Yargıtay içtihatlarına ve öğretideki görüşlere aykırı olarak, “...tüm yasal haklarım saklıdır...” cümlesinin genel bir ifade olduğu ve dolayısıyla çekince sayılamayacağı görüşünü benimsemiştir.

Reservation (reservation clause) is a right of the creditor, which can be defined as a state?ment of will preventing the debt to be wholly dissolved. This concept, which is generally iden?tified with the disciplines of law of obligations and commercial law, is also practiced in labor law from time to time; the right of reservation in the employment relationship is mostly used by the employee. Among the documents which usually include a reservation clause by the em?ployee; written notice of terminations known as resignation in practice bare an importance. The reservation ensures that the employee’s notice of termination or improper termination trans?forms to a rightful and immediate termination of the employee or an improper or unfair termi?nation of the employer; thus, the employee is not deprived of the receivables and rights due to termination, such as severance pay, notice compensation and reinstatement request. In the established application of the Court of Cassa?tion, the validity of the written resignations con?taining reservations is carefully scrutinized and in this context, there is no distinction between the general and special nature of the statement contained in the reservation. However, the İs?tanbul Court of Appeals, Division 29, contrary to the Court of Cassation’s case law and the opin?ions in the doctrine; has adopted the view in a dispute that the employee’s statement in the written resignation as “... all my legal rights are reserved...” is a general expression and therefore cannot be considered as reservation.
The Problem With The Validity of Termination Notice (Resignation) of The Employee Which Include Reservation (Reservation Clause)